Non-linear relationship between sleep duration and blood pressure in children with short stature - Zhao, Qianqian; He, Mingming; Zhang, Mei; Chu, Yuntian; Ban, Bo (Frontiers in Pediatrics, 2023)
Background: Evidence regarding the relationship between sleep duration and blood pressure is controversial. Therefore, the aim of this study was to investigate the relationship between sleep duration and blood pressure in children with short stature.: A total of 1,085 participants with short stature were enrolled from the Affiliated Hospital of Jining Medical University in China. The variables involved in this study included sleep duration, anthropometric indicators and biochemical parameters. Sleep duration was evaluated in a face-to-face interview.The average age of the 1,085 selected participants was 10.2±3.5 years old, and approximately 763 (70.32%) of them were male. The results of adjusted linear regression showed that sleep duration was negatively associated with systolic blood pressure z scores (SBP-Z) and diastolic blood pressure z scores (DBP-Z) after adjusting for confounders (β -0.07, 95% CI -0.13, -0.01 P = 0.038; β -0.05, 95% CI -0.10, -0.01 P = 0.035, respectively). A nonlinear relationship was detected between sleep duration and blood pressure, including SBP-Z, DBP-Z and mean arterial pressure z scores (MAP-Z). The inflection point of the nonlinear relationship between sleep duration and SBP-Z is 10 hours, and the inflection point of DBP-Z and MAP-Z is 8 hours.This study revealed a nonlinear relationship between sleep duration and blood pressure in children with short stature. The findings suggest that the optimal sleep duration in children with short stature was 8 to 10 hours, and sleep durations either too short or too long were associated with increased blood pressure levels.